Explorations : an introduction to astronomy - Arny, Thomas T. (Boston : McGraw-Hill, 2000)
The cosmic landscape. History of astronomy. Backyard astronomy. Gravity and motion. Light and atoms. The earth. Telescopes. Keeping time. The Moon. Survey of the solar system. The terrestrial planets. The outer planets. Meteors, Asteroids, and Comets. The sun, our star. Measuring the properties of stars. Stellar evolution....
Includes index.
Keywords: Astronomy; Astronomy